2014
DOI: 10.9734/ijpss/2014/12102
|View full text |Cite
|
Sign up to set email alerts
|

Root Properties of Plants Used for Soil Erosion Control in the Usambara Mountains, Tanzania

Abstract: Plant roots may have a strong erosion-reducing effect. However, little is known about root characteristics of tropical plants used for erosion control. A study was thus conducted in the Western Usambara Mountains, Tanzania to investigate rooting characteristics of Mwango et al.; IJPSS, Article no. IJPSS.2014.12.007 1568 Guatemala grass (Tripsacum andersonii), Napier grass (Pennisetum purpureum) and Tithonia shrub (Tithonia diversifolia), also referred to as wild sunflower, and to evaluate their potential fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…In most cases, however, plant roots are used to stabilize terrace edge. In the Usambara Mountains, Guatemala grass is grown for dual purpose, to control soil erosion and as a source of livestock fodder [127].…”
Section: Contour Farmingmentioning
confidence: 99%
“…In most cases, however, plant roots are used to stabilize terrace edge. In the Usambara Mountains, Guatemala grass is grown for dual purpose, to control soil erosion and as a source of livestock fodder [127].…”
Section: Contour Farmingmentioning
confidence: 99%
“…Differences in the erosion-reducing potential of different plant root systems call for a selection of the most appropriate plant species in programs of erosion control or hillslope stabilization (e.g. De Baets et al, 2007bBaets et al, , 2009Stokes et al, 2009;Reubens et al, 2011;Burylo et al, 2014;Mwango et al, 2014). However, the extrapolation of the relationships between root properties and erosion rates, observed in individual case studies, to other sites, with differences in climate, root and soil characteristics, remains difficult (Stokes et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Landholdings are diminishing due to human and animal population increase hence increased land use competition which poses an unformidable challenge to smallholder dairy farmers to choose whether to grow crops or pasture in limited land units. Mwango et al, (2014) in their study also found out that in Usambara Mountains in northern Tanzania the average farm size of 1.4 ha and farmers have opted to grow food crops and vegetables with pasture being restricted only around farm boundaries and contour strips. In Uganda and the East African region, most rural households are poor and cannot afford feed technological costs given the high poverty incidences (Aikaeli, 2010).…”
Section: The Socio-economic Factors Associated With Adoption Of Suppl...mentioning
confidence: 94%